Symptoms of common mental disorders in professional rugby: An international observational descriptive study - Gouttebarge, V.; Hopley, P.; Kerkhoffs, G.; Verhagen, E.; Viljoen, W.; Wylleman, P.; Lambert, M. I. (International Journal of Sports Medicine, 2017)
The aim of the study was to determine the prevalence of symptoms of common mental disorders among professional rugby players across countries. A cross-sectional analysis of the baseline questionnaires from an ongoing prospective cohort study was conducted. Nine national players` associations and three rugby unions distributed questionnaires based on validated scales for assessing symptoms of common mental disorders. Among the whole study sample (N=990; overall response rate of 28%), prevalence (4-week) of symptoms of common mental disorders ranged from 15% for adverse alcohol use to 30% for anxiety/depression. These findings support the prevalence rates of symptoms of common mental disorders found in previous studies among professional (i. e., elite) athletes across other sports, and suggestions can be made that the prevalence of symptoms of anxiety/depression seems slightly higher in professional rugby than in other general/occupational populations. Awareness of the prevalence of symptoms of common mental disorders should be improved in international rugby, and an interdisciplinary approach including psychological attention should be fostered in the medical care of professional rugby players. Adequate supportive measures to enhance awareness and psychological resilience would lead not only to improved health and quality of life among rugby players but arguably to enhanced performance in rugby.